2010
DOI: 10.1002/gps.2410
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well‐being, social support, and age‐related functioning among the very old in China

Abstract: Both social support from family members and cognitive function appear to be key factors associated with quality of life among the very old in China. Further research is needed among very old populations to confirm the importance of these variables and to examine potential cross-cultural differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 24 publications
5
56
2
3
Order By: Relevance
“…Qualitative research and quantitative studies can both make important contributions to the study of cultural influences on social support network and health outcome processes (as well as to the larger area of social support and health research). While quite a bit research in the area of social network support and health outcomes has been conducted in a variety of countries around the world, most of the research has been conducted in a relatively small number of countries in Europe and Asia (mainly China) (Van Tilburg, 1998;Sun et al, 2007;Deng et al, 2010;Rao et al, 2012).…”
Section: A Research Agenda For the Study Of Social Network Support Anmentioning
confidence: 99%
“…Qualitative research and quantitative studies can both make important contributions to the study of cultural influences on social support network and health outcome processes (as well as to the larger area of social support and health research). While quite a bit research in the area of social network support and health outcomes has been conducted in a variety of countries around the world, most of the research has been conducted in a relatively small number of countries in Europe and Asia (mainly China) (Van Tilburg, 1998;Sun et al, 2007;Deng et al, 2010;Rao et al, 2012).…”
Section: A Research Agenda For the Study Of Social Network Support Anmentioning
confidence: 99%
“…The average age of these populations has been under 90 years. There are some studies on the oldest-old, which include the effect of social networks on cognitive function (Cherry et al, 2013;Cho, Martin, & Poon, 2014;Deng, Hu, Wu, Dong, & Wu, 2010), but few studies have focused only on the association between social networks, social contacts, and cognitive impairment in the individuals aged 90 years or older.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have found individual characteristics (such as gender, age, and education) (24)(25)(26), social support (26,27), social belonging (28), economic openness (29), and atmospheric pollution (30) to be associated with SWB among urban Chinese people, research focusing specifically on the neighborhood environment and SWB among elders in China has been limited. In fact, we could only find one such study (27), and this study did not examine individual, physical, and social environmental characteristics simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we could only find one such study (27), and this study did not examine individual, physical, and social environmental characteristics simultaneously. The objective of the present study is to address a gap in the SWB literature with a cross-sectional study examining the effects of neighborhood social cohesion, social interaction, aesthetic quality (AQ), and walkability on SWB in a sample of elders from Shanghai, China.…”
Section: Introductionmentioning
confidence: 99%